Некоторые преимущества сетевых педагогических сообществ - Тихонова, Л.В. (My University, 2016)
Relevance. Development of network pedagogical associations determines modern progress of education trends on the whole, extending possibilities of teachers to participate in network regional, international projects, promote the level, divided and adopt experience etc. Goal: opening of creative potential, development of research type of thinking. A network association renders timely psychological, methodical support, gives an opportunity of positive and effective cooperation of teachers in a network the Internet, psychologically influences a teacher the same on "success".
Keywords: network association; problems; advantages